2012
DOI: 10.1785/0120110262
|View full text |Cite
|
Sign up to set email alerts
|

Interseismic Deformation and Earthquake Hazard along the Southernmost Longitudinal Valley Fault, Eastern Taiwan

Abstract: About half of the 8 cm=yr of oblique convergence across the active con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…This model highlights the distinction between sections of the fault that are creeping and the ones that remain locked. As previously recognized, the southern portion of the fault is creeping near the surface [ Angelier et al , ; Lee et al , , , , ; Hsu and Burgmann , ; Lee et al , ; Chang et al , ; Cheng et al , ; Hsu et al , ; Huang et al , ; Peyret et al , ; Champenois et al , ; Chen et al , ; Chuang et al , ]. Our study highlights that, on the contrary, the northern part is mostly locked.…”
Section: Secular Interseismic Modelsupporting
confidence: 80%
“…This model highlights the distinction between sections of the fault that are creeping and the ones that remain locked. As previously recognized, the southern portion of the fault is creeping near the surface [ Angelier et al , ; Lee et al , , , , ; Hsu and Burgmann , ; Lee et al , ; Chang et al , ; Cheng et al , ; Hsu et al , ; Huang et al , ; Peyret et al , ; Champenois et al , ; Chen et al , ; Chuang et al , ]. Our study highlights that, on the contrary, the northern part is mostly locked.…”
Section: Secular Interseismic Modelsupporting
confidence: 80%
“…According to GPS velocity data from 2001 to 2003, the Pingting Terrace is moving at an approximate rate of 28.6 mm/yr in the northwest direction (ERPN station). There's a significant velocity difference on both sides of the fault (approximately 16.9 mm/yr), suggesting a slight left-lateral oblique motion (Chuang et al, 2012). The MT-InSAR results from ALOS images taken between 2007 and 2010 show a reverse slip velocity of about 7 mm/yr for the Lichi Fault (PTF1) in the LOS direction, while the Chihshang Fault (PTF2) of the 2nd Terrace has a reverse activity rate of 20 mm/yr in the LOS direction (Deffontaines et al, 2017).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Strike-slip components are also observed in the fault activity. Previous studies have also indicated the presence of strike-slip components within the Pingting Terrace based on topographic features and geodetic monitoring (Shyu et al, 2008;Chuang et al, 2012). Accordingly, our research team employed the Riedel shear structures model to analyze the geometric relationships, regional stress, and principal shear directions of the surface ruptures within the Pingting Terrace.…”
Section: Riedel Shear Structure Analysismentioning
confidence: 99%